MARKETING INFORMATION SYSTEM FOR PURCHASING BOOK FOR LIBRARY;ASSISTING BUSINESS BUYING BEHAVIOUR IN EDUCATIONAL - Kristanto, Harianto (Duta Wacana Christian University, 2008)
Purchasing books for library in educational institution has many problems. The librarians as buyers can not buy books since she/ he does not have sense about the contents and objective of the needs. Students and lectures better and more capable to selecting books they need, but they do not have authorization and relevant decision to buy them. The buyers can solved the problems if they have support from marketing database or marketing information system. A marketing information system was analyzed and designed to assit libraries, lectures, students to communicate each other. The libraries make segmentation about categorized books, budget segmentation by topic, study programs, faculties, and major interest. This study proposed a design and a user interface to make a comfortable and precise decision in purchasing books, CRM concepts will be used as a communicating betwen the librarians and the user